Peroxide scavenging potential of ultraviolet-B-absorbing mycosporine-like amino acids isolated from a marine red alga Bryocladia sp. - Kannaujiya, Vinod K.; Richa, Vinod K.; Sinha, Rajeshwar P. (Frontiers in Environmental Science, 2014)
Ultraviolet-B (UV-B; 280-315 nm)-absorbing mycosporine-like amino acids (MAAs) were extracted and purified from a marine red alga Bryocladia sp. by using high performance liquid chromatography. We have detected four MAAs having retention times 3.23, 2.94, 3.56 and 2.67 min with absorbance maxima (λmax) at 323, 328, 335 and 340 nm respectively. The effect of UV-B on the induction of these MAAs was studied. In comparison to control, there was 3 - 22 % induction of MAAs after 12 and 24 h of UV-B exposure. Apart from MAAs, other pigments such as chl a, carotenoids and total proteins were inversely affected by UV-B irradiation. In addition, peroxide scavenging potential of these MAAs were also investigated. With 2 mM hydrogen peroxide (H2O2) concentration, only <5 % of MAAs were found to be affected. However, with the increased H2O2, 40-60 % decline in the MAAs concentration with a corresponding peak shifting towards the blue wavelength was recorded. In addition, most of the MAAs were found to be reacting slowly with increasing H2O2 (upto 10 mM) concentration after an incubation period of 5 and 30 min, which indicates the remarkable scavenging potential and stability of MAAs against oxidative stress. Thus, the isolated MAAs from marine red alga Bryocladia sp. may act as an efficient peroxide scavenger.